DNA Probe as Biosensor Candidate for Clavibacter michiganensis subsp. michiganensis on Tomato Plants - Hidayati, Muslihah Nur; Suranto; Susilowati, Ari (Jurnal Fitopatologi Indonesia, 2022)
The study was conducted to evaluate gene detection technique using a specific DNA probe to detect tomA gene in Clavibacter michiganensis subsp. michiganensis, a bacteria causing cancer in tomatoes. The probe was designed using Primer3Plus program, labeled with the non-radioactive molecule digoxigenin (DIG) and used in the hybridization method with the dot blot technique. The test samples consisted of two types, i.e. genomic DNA samples from pure bacterial cultures and from artificially infected tomato seeds with C. michiganensis subsp. michiganensis. Samples derived from pure bacterial cultures showed positive hybridization results at all levels of DNA concentration; while samples from tomato seeds only showed positive reactions at concentrations of 10, 8, 6, and 4 g L-1. This study concludes that the designed probe has the potential to be used in the development of biosensor-based detection methods for C. michiganensis subsp. michiganensis in tomato seeds and is quite specific because there is no cross-reaction with non-target bacterial groups.